2020
DOI: 10.5194/acp-20-12347-2020
|View full text |Cite
|
Sign up to set email alerts
|

The impact of weather patterns and related transport processes on aviation's contribution to ozone and methane concentrations from NO<sub><i>x</i></sub> emissions

Abstract: Abstract. Aviation-attributed climate impact depends on a combination of composition changes in trace gases due to emissions of carbon dioxide (CO2) and non-CO2 species. Nitrogen oxides (NOx = NO + NO2) emissions induce an increase in ozone (O3) and a depletion of methane (CH4), leading to a climate warming and a cooling, respectively. In contrast to CO2, non-CO2 contributions to the atmospheric composition are short lived and are thus characterised by a high spatial and temporal variability. In this study, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 37 publications
4
21
0
Order By: Relevance
“…SCAV calculates the transfer of species into and out of rain and cloud droplets using the Henry's law equilibrium, acid dissociation equilibria, oxidation-reduction reactions, heterogeneous reactions on droplet surfaces, and aqueous-phase photolysis reactions (Tost et al, 2006). As mentioned earlier and as demonstrated by Rosanka et al (2021a), in-cloud OVOC oxidation significantly influences the atmospheric composition. However, the ordinary differential equations (ODE) systems resulting from the combination of gas-phase and in-cloud aqueous-phase suffer from (1) a higher stiffness due to fast acid-base equilibria and phase-transfer reactions and (2) load imbalance on high-performance computing (HPC) systems due to the sparsity of clouds.…”
Section: Atmospheric Chemistrymentioning
confidence: 97%
See 3 more Smart Citations
“…SCAV calculates the transfer of species into and out of rain and cloud droplets using the Henry's law equilibrium, acid dissociation equilibria, oxidation-reduction reactions, heterogeneous reactions on droplet surfaces, and aqueous-phase photolysis reactions (Tost et al, 2006). As mentioned earlier and as demonstrated by Rosanka et al (2021a), in-cloud OVOC oxidation significantly influences the atmospheric composition. However, the ordinary differential equations (ODE) systems resulting from the combination of gas-phase and in-cloud aqueous-phase suffer from (1) a higher stiffness due to fast acid-base equilibria and phase-transfer reactions and (2) load imbalance on high-performance computing (HPC) systems due to the sparsity of clouds.…”
Section: Atmospheric Chemistrymentioning
confidence: 97%
“…The degradation of methane (CH 4 ) and non-methane hydrocarbons (NMHC) in the atmosphere accounts for almost half of the global CO sources (Zheng et al, 2019). In the atmosphere, CO mainly reacts with OH, and the EMAC estimates by Lelieveld et al (2016) and more recently by Rosanka et al (2021a) show that CO largely determines the atmospheric oxidation capacity. To a lesser extent, CO is deposited (Stein et al, 2014).…”
Section: Comparison To Iasi Co Retrievalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, aviation NO x emissions lead to a formation of O 3 and a depletion of methane (CH 4 ). Recently, Rosanka et al (2020a) showed that the enhancement in O 3 is limited by the background concentrations of NO x and HO x . If enough HO x is available, a lower background NO x concentration results in a higher O 3 gain.…”
Section: The Influence Of In-cloud Ovoc Oxidation During the Indonesian Peatland Firesmentioning
confidence: 99%